Rare Earth and Platinum Group Elements In Sub-Saharan Africa and Global Health: The Dark Side of the Burgeoning of Technology - Chiara Frazzoli; Beatrice Bocca; Beatrice Battistini; Flavia Ruggieri; Joaquim Rovira; Cecilia Nwadiuto Amadi; Samuel James Offor; Orish E Orisakwe (SAGE Publishing, 2024)
Despite steady progress in the development and promotion of the circular economy as a model, an overwhelming proportion of technological devices discarded by the Global North still finds its way to the Global South, where technology-related environmental health problems start from the predation of resources and continue all the way to recycling and disposal. We reviewed literature on TCEs in sub-Saharan Africa (SSA), focussing on: the sources and levels of environmental pollution; the extent of human exposure to these substances; their role in the aetiology of human diseases; their effects on the environment. Our review shows that even minor and often neglected technology-critical elements (TCEs), like rare earth elements (REEs) and platinum group elements (PGEs), reveal the environmental damage and detrimental health effects caused by the massive mining of raw materials, exacerbated by improper disposal of e-waste (from dumping to improper recycling and open burning). We draw attention of local research on knowledge gaps such as workable safer methods for TCE recovery from end-of-life products, secondary materials and e-waste, environmental bioremediation and human detoxification. The technical and political shortcomings in the management of TCEs in SSA is all the more alarming against the background of unfavourable determinants of health and a resulting higher susceptibility to diseases, especially among children who work in mines and e-waste recycling sites or who reside in dumping sites.This paper demonstrates, for the first time, that the role of unjust North-South dynamics is evident even in the environmental levels of minor trace elements and that the premise underlying attempts to solve the problem of e-waste dumped in Africa through recycling and disposal technology is in fact misleading. The influx of foreign electrical and electronic equipments should be controlled and limited by clearly defining what is a 'useful' second-hand device and what is e-waste; risks arising from device components or processing by-products should be managed differently, and scientific uncertainty and One Health thinking should be incorporated in risk assessment.